Productivity of corn (Zea mays) under varying drought duration and nitrogen application at La, Trinidad, Benguet - Pablo, J P; Awidan, G M; Cacal, D M (Asian Journal of Agriculture and Rural Development, 2025)
This study investigates the impact of varying durations of drought and different nitrogen application strategies on corn. The study employed a Split Plot Design with three replications. Main plots (levels and timing of nitrogen) included NO FERT (no fertilizer), RR+OA (recommended rate at one-time application), RR+SA (split application), RR+50N+OA (50% nitrogen), and RR+50N+SA. Subplots tested drought durations of 10, 15, and 20 days (DD). Data were analyzed using two-way ANOVA, and treatment mean differences were assessed using LSD at the 5% significance level. Significant (P < 0.05) effects of fertilizer were observed on leaf area (LA), total number of kernel rows per ear (TNE), and chlorophyll content (CC). Drought significantly affected plant height (PH), LA, root weight (RW), ear length (EL), ear weight (EW), total number of kernels per row (TKR), TNE, total weight of corn ears (TWE), CC, drought score (DS), and recovery rate (RR). No significant differences were found in the interaction of drought and fertilizer, except for root weight. Subjecting plants to longer drought durations showed more negative effects on productivity. The recommended rate plus 50% of nitrogen at one-time application, along with the recommended rate and split application, are the best levels and timing of application when exposed to drought during the vegetative stage.